2011
DOI: 10.1007/s13233-011-1116-1
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite membranes consisting of poly(vinyl chloride) graft copolymer and surface-modified silica nanoparticles

Abstract: A graft copolymer of poly(vinyl chloride)-graft-poly(oxyethylene methacrylate) (PVC-g-POEM) was synthesized via atom transfer radical polymerization (ATRP), and fumed silica (SiO 2 ) nanoparticles were modified by grafting POEM via a three-step synthetic approach. The resultant graft copolymer and modified SiO 2 nanoparticles were solution blended to prepare PVC-g-POEM/SiO 2 -POEM nanocomposite membranes. Uniform distribution of SiO 2 -POEM nanoparticles in the membranes and microphase-separated morphology wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Successful synthesis of PDMS- g -PEOM comb copolymer was confirmed by FT-IR spectroscopy as shown in Figure a. The presence of methacrylate in POEM with a molecular weight of 500 g/mol was confirmed by the sharp peaks at 1717 and 1637 cm –1 caused by the stretching vibration of the carbonyl group (-CO) in the ester and stretching unsaturated double bond (-CC), respectively . However, the presence of methacrylate in PDMS-mMA with a molecular weight of 10000 g/mol was not clearly observed due to the much lower concentration of terminal methacrylate groups than repeating units of PDMS.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Successful synthesis of PDMS- g -PEOM comb copolymer was confirmed by FT-IR spectroscopy as shown in Figure a. The presence of methacrylate in POEM with a molecular weight of 500 g/mol was confirmed by the sharp peaks at 1717 and 1637 cm –1 caused by the stretching vibration of the carbonyl group (-CO) in the ester and stretching unsaturated double bond (-CC), respectively . However, the presence of methacrylate in PDMS-mMA with a molecular weight of 10000 g/mol was not clearly observed due to the much lower concentration of terminal methacrylate groups than repeating units of PDMS.…”
Section: Resultsmentioning
confidence: 94%
“…The presence of methacrylate in POEM with a molecular weight of 500 g/mol was confirmed by the sharp peaks at 1717 and 1637 cm −1 caused by the stretching vibration of the carbonyl group (-CO) in the ester and stretching unsaturated double bond (-CC), respectively. 23 However, the presence of methacrylate in PDMS-mMA with a molecular weight of 10000 g/mol was not clearly observed due to the much lower concentration of terminal methacrylate groups than repeating units of PDMS. The peaks of PDMS-mMA at 1280 and 790 cm −1 are due to symmetric CH 3 deformation and Si(CH 3 ) 2 rocking, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the past few years, GNPs were proposed as promising candidates for gas separation membranes. Membranes of self-suspended poly­(methyl acrylate)-grafted silica nanoparticles exhibited elevated gas permeability with respect to the corresponding linear polymer chains . The effectiveness of these membranes depended on the molar mass of the tethered chains in a nonmonotonic way.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zhu et al find that addition of nanosilica into PVC matrix improves the mechanical properties of the NCs greatly [15]. Ahn et al reported that introduction of organically modified SiO 2 NPs to PVC matrix caused excellent mechanical properties for the resulting NCs [16].…”
Section: Introductionmentioning
confidence: 99%